2018
DOI: 10.1016/j.ebiom.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Cancer: Existing and New Hypotheses for a Causal Connection

Abstract: Existing explanations of obesity-associated cancer emphasise direct mutagenic effects of dietary components or hormonal imbalance. Some of these hypotheses are reviewed briefly, but recent evidence suggests a major role for chronic inflammation in cancer risk, possibly involving dietary content. These ideas include the inflammation-induced activation of the kynurenine pathway and its role in feeding and metabolism by activation of the aryl hydrocarbon receptor (AHR) and by modulating synaptic transmission in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
158
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(163 citation statements)
references
References 259 publications
(309 reference statements)
1
158
0
4
Order By: Relevance
“…The most recent data reports ~70% of the American population is overweight (body mass index (BMI) ≥ 25 kg/m 2 ) and ~35% is obese (BMI ≥30 kg/m 2 ) [2,3]. The need to reduce obesity stems from the increased risk of comorbidities such as cardiovascular disease, type 2 diabetes, asthma, certain cancers, and various other diseases [4][5][6]. A report compiled of 57 prospective analyses of nearly a million adults, showed that obesity can decrease a person's life span up to 10 years [7].…”
Section: Role Of Adipose Tissue In Systemic Energy Homeostasismentioning
confidence: 99%
“…The most recent data reports ~70% of the American population is overweight (body mass index (BMI) ≥ 25 kg/m 2 ) and ~35% is obese (BMI ≥30 kg/m 2 ) [2,3]. The need to reduce obesity stems from the increased risk of comorbidities such as cardiovascular disease, type 2 diabetes, asthma, certain cancers, and various other diseases [4][5][6]. A report compiled of 57 prospective analyses of nearly a million adults, showed that obesity can decrease a person's life span up to 10 years [7].…”
Section: Role Of Adipose Tissue In Systemic Energy Homeostasismentioning
confidence: 99%
“…; Khalid and Holguin ; Stone et al. ). Indeed, a report of 57 prospective analyses comprised of nearly a million adults, showed that obesity can decrease a person's life span by up to 10 years (Prospective Studies et al.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity has been one of the fastest growing factors negatively influencing human health over the last several decades (Flegal et al 2012;Ogden et al 2015;CDC, 2016). In particular, obesity increases the risk for type 2 diabetes, insulin resistance, cardiovascular disease, certain cancers, infertility, asthma, and many other diseases (Shoelson et al 2007; Khalid and Holguin 2018;Stone et al 2018). Indeed, a report of 57 prospective analyses comprised of nearly a million adults, showed that obesity can decrease a person's life span by up to 10 years (Prospective Studies et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This cannot be solely explained by targeted cancer screening for these types of cancer (mammography, colon/sigmoidoscopy, PSA test) or hormone levels alteration due to HIV infection . Overweight/obesity is less prevalent in people living with HIV than in general population, and that is a proposed risk factor for gastrointestinal tract tumors, breast, endometrial and renal cancers . This requires further investigation with a direct comparison of HIV‐infected people with body mass index‐matched uninfected people.…”
Section: Hiv and Cancer Risks In The Haart Eramentioning
confidence: 99%
“…42 Overweight/obesity is less prevalent in people living with HIV than in general population, and that is a proposed risk factor for gastrointestinal tract tumors, breast, endometrial and renal cancers. 13,43 This requires further investigation with a direct comparison of HIV-infected people with body mass index-matched uninfected people. These trends may also be due to viral-host interaction.…”
Section: Non-aids Defining Cancersmentioning
confidence: 99%